The Influence of Product Price and Service Quality on The Decision to Purchase Iron Steel at Pt Sinar Bangun Tata Semesta in West Jakarta - jefri, Jefpri Parulian; Carolina F. Sembiring; Desideria Regina (Universitas Kristen Indonesia, 2024)
These studies aim to determining the effects of Products, Prices and Services Quality both simultaneously and simultaneously on Purchases Decision. The independent variable in these studies are Products Quality, Prices, and Services Quality, while dependent variable is Purchases Decision. These studies used a random sampling methods with a total samples of 35 respondent, especially DKI Jakarta. Methods of data analyst used SPSS software versions 25 The result of these studies proves that partially or simultaneously, product quality has a significancy effects on purchasing decisions, while prices have no significancy effects on purchasing decision, and service quality has a significancy effects on purchasing decision. Keywords: Product Quality, Price, Service Quality, Purchasing Decision